2019
DOI: 10.1111/1759-7714.13036
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic completion right lower lobectomy after anteromedial basilar segmentectomy in early‐stage lung cancer

Abstract: This report describes the surgical management of a male patient with early‐stage lung cancer who underwent thoracoscopic completion right lower lobectomy after previously undergoing sublobar resection for multifocal ground glass nodules of the lung. Perioperative considerations associated with the management of dense pulmonary hilar adhesions and the techniques used are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…7) in which VATS was used to perform CL has been reported in a previous study. 9 Herein, we describe another case of thoracotomy for CL (No. 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7) in which VATS was used to perform CL has been reported in a previous study. 9 Herein, we describe another case of thoracotomy for CL (No. 5).…”
Section: Resultsmentioning
confidence: 99%
“… 7 In terms of technical issues, some authors have addressed the use of simultaneous division of the PA and lung parenchyma with a stapler to manage tight adhesions. 8 , 9 Simultaneous stapling of the bronchus and PA is generally not preferred because of the risk of staple line bursts, bronchopleural fistula, and massive bleeding; however, no adverse events resulting from simultaneous stapling have been reported in the literature. Lewis et al encountered no significant stapling‐related complications in 400 consecutive lobectomies, all performed using simultaneous stapling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table S 1 summarizes previously reported cases of completion lobectomy after segmentectomy for pulmonary malignancy [ 4 , 5 ]. We excluded reports of completion lobectomy after wedge resection [ 6 ] or after segmentectomy due to a short surgical margin [ 7 ] or unanticipated lymph node metastasis [ 8 ]. Omasa et al reported 11 patients (9 primary lung cancer, 2 metastatic lung cancer) who underwent completion lobectomy due to perioperative complication ( n = 3), unanticipated lymph node metastasis ( n = 3), or appearance of malignancy (2 local recurrence and 3 new malignancy) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes previously reported cases of completion lobectomy after segmentectomy for pulmonary malignancy [4,5]. We excluded reports of completion lobectomy after wedge resection [6] or after segmentectomy due to a short surgical margin [7] or unanticipated lymph node metastasis [8].…”
Section: Discussionmentioning
confidence: 99%